Effects of knee cooling on in vivo patellar tendon mechanical properties - Alegre, L. M.; Hasler, M.; Wenger, S.; Nachbauer, W.; Csapo, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Controversy exists regarding the temperature dependency of tendon mechanical properties (Kubo et al., 2005; Muraoka et al., 2008). Specifically, no studies have investigated the effects of knee cooling on the in vivo human patellar tendon. Therefore, the aim of this study was to assess the material properties of the patellar tendon before and after local ice application. METHODS: Twenty young, healthy women volunteered for the study. B-mode ultrasonography was used to record patellar tendon elongation during isometric ramp contraction of the knee extensors (5-7 s, 90° knee angle), and calculate tendon stiffness, Young`s modulus as well as maximum strain and stress. Skin temperature was measured by infrared thermometry. Data were acquired before and after 30 min of local icing of the knee joint and compared by paired samples t-tests. RESULTS: After cold exposure, skin temperature at the patellar tendon dropped from 26.1±1.7 to 9.3±2.1°C. Tendon stiffness and Young`s modulus increased from 2189±551 to 2705±902 N/mm (+24%, p=0.007) and 1.32±3.4 to 1.60±4.9 GPa (+21%, p=0.010), respectively. Tendon strain decreased from 8.6±1.6% to 7.8±1.4% (-10%, p=0.004). A small, albeit significant reduction in maximum tendon force was observed (from 5148±1176 N to 4957±1048 N, -3.7%, p=0.03). DISCUSSION: Our data show a significant impact of local cold exposure on in vivo patellar tendon mechanical properties, especially on tendon stiffness and Young`s modulus. The observed tendon stiffening may influence the operating range of sarcomeres, limiting the force generation capacity of knee extensor muscles acting on the descending limb of the length-tension curve. On the other hand, the increased stiffness might benefit rate of force development, thus countering the consequences of reduced enzymatic activity described for muscles under cold exposure (Drinkwater & Behm, 2007). Even more, a stiffer tendon would facilitate more accurate joint control (Rack & Ross, 1984). In conclusion, we found a significant impact of local cold exposure on in vivo patellar tendon mechanical properties, which is assumed to influence quadriceps muscle function, especially in explosive contractions.